Construcción de un cuestionario de creencias actitudinales sobre el comportamiento suicida: el CCCS-18 - Ruiz Hernández, José Antonio; Navarro-Ruiz, Juana M.ª; Torrente Hernández, Ginesa; Rodríguez González, ángel (Psicothema, 2005)
Construction of an attitudinal beliefs questionnaire towards suicidal behaviour. A new questionnaire has been developed in order to have a brief and manageable instrument for the assessment of attitudes towards suicide. The original pool of 60 items, constructed and reviewed using accurate standards, was filled out by 219 subjects. The analyses concluded with the selection of 18 items with an internal structure of four factors. Both the questionnaire and all 4 factors show a high internal consistency (between 0,73 and 0,87). The results indicate that the four dimensions found with this instrument might be closely related with the propensity to suicidal behaviour. Finally, strategies for a further psychometric development of the instrument are suggested.